FROM ETHICS OF JUSTICE AND SUFFERING TO ETHICS OF FREE AND UNCONDITIONED PERSONALITY - V. E. Gromov (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The author regards the distinction between spiritual meaning inherent to ethics of justice and ethics of a free and unconditioned personality. He substantiates that the ethics of justice is insufficient for spiritual realization of man and it is a mental base of “suffering consciousness”. The author points at the absolute moral advantage of spiritual direction of culture. Methodology. The author connected methodological approach to the research into the spiritual quality of morality with fundamental distinction between the highest and the lowest levels of morality and with high degree of autonomy characterizing of spiritual directed consciousness. Scientific novelty. The article regards “eternal” and steady motivation of a man for justice and dignity. This problem remains topical in our days in conditions of intensive search for optimal correlation between the factors of humanity and violence in moral practice of modern civilized society. Conclusions. The ascension of modern social morality to the level of spiritual ethics is improbable, but, taking into account the metaphysical understanding of the essence of man, it is possible. The ethics of a free and unconditional person has a great potential in its influence on social moral. It leads to universal transformation of people’s attitude to themselves and to the surrounding reality. Utopian character and unfeasibility of spiritual ethics idea are determined by its independence from empirical conditions and by the difficulty concerned with conscious self-transformation of conditioned personality. The author intends to point out the “absolute” advantage of spiritually directed culture in realizing the opportunity of the moral evolution of society towards spirituality.